The Liquid Chromatographic Determination of Chlorogenic and Caffeic Acids in Xu Duan (Dipsacus asperoides) Raw Herb. (4th May 2014) - Pearson, Jarryd L.; Lee, Samiuela; Suresh, Harsha; Low, Mitchell; Nang, Marnilar; Singh, Swastika; Lamin, Franklin; Kazzem, Magdy; Sullivan, Shaun; Khoo, Cheang S.
Abstract : A validated analytical method is reported for the analysis of chlorogenic and caffeic acids in Xu Duan ( Dipsacus asperoides ) in the dried raw herb. The ground samples were extracted by ultrasonication in water and the extract was analysed by LC-PDA with identity confirmation by (+)ESI-MS/MS. A C18 column was used with a 0.1% aqueous formic acid : methanol gradient mobile phase. The analytes were quantified 325 nm. With the MS detector, using the chlorogenic acid precursor ion with m/z 354, ions with m/z 191, and 85 were produced. For caffeic acid the precursor ion with m/z 181, ions with m/z 163, 135, and 89 were produced. The amount of chlorogenic and caffeic acids in the raw herb was found to be 4.46 and 0.63 mg/g, respectively, and the method LOD was 0.13 and 0.02 mg/g, respectively.